2020
DOI: 10.1136/bmjgh-2020-002689
|View full text |Cite
|
Sign up to set email alerts
|

Engaging culture and context in mhGAP implementation: fostering reflexive deliberation in practice

Abstract: In 2002, WHO launched the Mental Health Gap Action Programme (mhGAP) as a strategy to help member states scale up services to address the growing burden of mental, neurological and substance use disorders globally, especially in countries with limited resources. Since then, the mhGAP program has been widely implemented but also criticised for insufficient attention to cultural and social context and ethical issues. To address this issue and help overcome related barriers to scale-up, we outline a framework of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 69 publications
0
15
0
1
Order By: Relevance
“…While this movement was lauded by many, others noted that the universal adoption of these models risked neglecting local views on distress and healing that had served the needs of many communities around the world and ignoring the numerous limitations (and harms) of these models. Efforts continue to be made to find a way to avoid the problems associated with these ‘western’ modes of diagnosis and care while working to identify their strengths and integrate local approaches to healing and care 28 29. It is this type of critical engagement with approaches that is needed when using LMIC in global scholarship.…”
Section: Moving Towards Creative and Targeted Categorisationmentioning
confidence: 99%
“…While this movement was lauded by many, others noted that the universal adoption of these models risked neglecting local views on distress and healing that had served the needs of many communities around the world and ignoring the numerous limitations (and harms) of these models. Efforts continue to be made to find a way to avoid the problems associated with these ‘western’ modes of diagnosis and care while working to identify their strengths and integrate local approaches to healing and care 28 29. It is this type of critical engagement with approaches that is needed when using LMIC in global scholarship.…”
Section: Moving Towards Creative and Targeted Categorisationmentioning
confidence: 99%
“…Domains included examining concepts of wellness and illness, exploring systems of care, recognising formal and informal care systems, and considering the ethical space of power dynamics and decision making. 13…”
Section: Local Adaptation or Contextualisationmentioning
confidence: 99%
“…However, stigma, cultural differences and differing perspective on treatments can be barriers to mhGAP-IG implementation and use 17 39. Following the recommendation to locally adapt the mhGAP-IG is not always described; a recent framework has been published, which guides mhGAP-IG cultural and contextual adaptation 48. While we previously identified 15 studies reporting local mhGAP-IG adaptation or contextualisation,17 39 only three non-mhGAP-IG studies identified by this review discussed intervention adaptation.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 98%